Security of Networks and Services in an All-Connected World: 11th IFIP WG 6.6 International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2017, Zurich, Switzerland, July 10-13, 2017, Proceedings AIMS: IFIP International Conference on Autonomous Infrastructure, Management and Security - Daphne Tuncer (Lecture Notes in Computer Science, 2017)
This book constitutes the refereed proceedings of the 11th IFIP WG 6.6 International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2017, held in Zurich, Switzerland, in July 2017. The 8 full papers presented together with 11 short papers were carefully reviewed and selected from 24 submissions. The papers are organized in the following topical sections: security management; management of cloud environments and services, evaluation and experimental study of rich network services; security, intrusion detection, and configuration; autonomic and self-management solutions; and methods for the protection of infrastructure.